Correlation of 18F-Fluorodeoxyglucose Positron Emission Tomography Parameters with Patterns of Disease Progression in Locally Advanced Pancreatic Cancer after Definitive Chemoradiotherapy. Issue 6 (June 2017) - Wilson, J.M.; Mukherjee, S.; Brunner, T.B.; Partridge, M.; Hawkins, M.A.
Abstract: Aims: A proportion of patients with pancreatic cancer never develop metastatic disease. We evaluated a role for 18 F-fluorodeoxyglucose positron emission tomography (FDG-PET) in identifying a subset of patients with locally advanced pancreatic cancer (LAPC) who never develop metastatic disease and only experience local disease and may therefore benefit from local treatment intensification. Material and methods: Patients with histologically confirmed LAPC entered a single-centre phase II study of definitive upfront chemoradiotherapy (CRT). All patients underwent FDG-PET/CT before and 6 weeks after CRT. Tumour volume, standardised uptake values (SUVmax, SUVpeak, SUVmean, SUVmedian ) and total lesion glycolysis (TLG) were measured on each scan and the response in each parameter was evaluated. The presence or absence of metastatic disease was noted on contrast-enhanced CT carried out every 3 months for 1 year and then at clinician discretion. Results: Twenty-three patients with LAPC were recruited; 17/23 completed treatment and had interpretable sequential imaging. Twenty-four per cent of patients only ever experienced local disease. Median pre-CRT FDG-PET parameters were significantly lower in patients with local disease only during follow-up compared with those who developed metastatic disease: SUVmax 3.8 versus 8.6 ( P = 0.006), SUVpeak 2.5 versus 7.5 ( P = 0.002), SUVmean 1.8 versus 3.3 ( P = 0.001), SUVmedian 1.7 versus 3.0 ( P = 0.002), TLG 26.9 versus 115.9 ( P = 0.006). Tumour volume, post-CRT FDG-PET values and their relative change were not statistically different between local disease and metastatic disease groups. Receiver operating characteristic curves for pre-CRT FDG-PET parameters to predict those who never develop metastatic disease all had areas under the curve (AUCs) ≥ 0.932. Pre-CRT FDG-PET SUVmax < 6.2 predicted patients with local disease only during follow-up with 100.0% sensitivity and 92.3% specificity, 80.0% positive predictive value and 100% negative predictive value. Conclusions: Our findings suggest that patients with less FDG-avid tumours are less likely to metastasise and may therefore benefit from upfront local treatment intensification. Highlights: A proportion of patients with locally advanced pancreatic cancer do not develop detectable metastatic disease. Locally advanced pancreatic tumours that are not FDG-avid tend not to metastasise and patients die because of locally progressive disease. This subgroup of patients may benefit from treatment interventions that aim to optimise local control. FDG-PET SUVmax offers a good summary of the metabolic activity of pancreatic tumours.